Bacterial cytolysin during meningitis disrupts the regulation of glutamate in the brain, leading to synaptic damage. - Carolin Wippel; Jana Maurer; Christina Förtsch; Sabrina Hupp; Alexandra Bohl; Jiangtao Ma; Timothy J Mitchell; Stephanie Bunkowski; Wolfgang Brück; Roland Nau; Asparouh I Iliev (PLoS Pathogens)
Streptococcus pneumoniae (pneumococcal) meningitis is a common bacterial infection of the brain. The cholesterol-dependent cytolysin pneumolysin represents a key factor, determining the neuropathogenic potential of the pneumococci. Here, we demonstrate selective synaptic loss within the superficial layers of the frontal neocortex of post-mortem brain samples from individuals with pneumococcal meningitis. A similar effect was observed in mice with pneumococcal meningitis only when the bacteria expressed the pore-forming cholesterol-dependent cytolysin pneumolysin. Exposure of acute mouse brain slices to only pore-competent pneumolysin at disease-relevant, non-lytic concentrations caused permanent dendritic swelling, dendritic spine elimination and synaptic loss. The NMDA glutamate receptor antagonists MK801 and D-AP5 reduced this pathology. Pneumolysin increased glutamate levels within the mouse brain slices. In mouse astrocytes, pneumolysin initiated the release of glutamate in a calcium-dependent manner. We propose that pneumolysin plays a significant synapto- and dendritotoxic role in pneumococcal meningitis by initiating glutamate release from astrocytes, leading to subsequent glutamate-dependent synaptic damage. We outline for the first time the occurrence of synaptic pathology in pneumococcal meningitis and demonstrate that a bacterial cytolysin can dysregulate the control of glutamate in the brain, inducing excitotoxic damage.